The Virtual Toxicology Journal Club: the Dissemination and Discussion of Noteworthy Manuscripts Using Twitter - Chai, Peter R. (J Med Toxicol, 2018)
BACKGROUND: Twitter-based chat groups (tweetchats) structured as virtual journal clubs have been demonstrated to provide value to learners. In order to promote topics in medical toxicology, we developed the #firesidetox tweetchat as a virtual journal club to discuss and disseminate topics in medical toxicology. METHODS: A group of medical toxicologists from the American College of Medical Toxicology (ACMT) Public Affairs Committee and editorial board of the Journal of Medical Toxicology (JMT) developed a quarterly one hour tweetchat featuring JMT manuscripts. We gathered basic twittergraphics and used a healthcare hashtag aggregator to measure the number of impressions, participants, and tweets per tweetchat session. A qualitative analysis of important themes from #firesidetox was also completed. RESULTS: During five tweetchats over 12 months, we attracted a mean of 23 participants generating a mean of 150 tweets per #firesidetox tweetchat. Tweets generated a mean of 329,200 impressions (unique user views): these impressions grew by 300% from the first through fifth #firesidetox. The majority of participants self-identified as medical toxicologists or physician learners. Although most were from the USA, participants also came from Australia, Poland, and Qatar. Most tweets centered on medical education and 7.9% tweets were learner-driven or questions asking for a medical toxicologist expert opinion. CONCLUSION: The #firesidetox attracted a diverse group of toxicologists, learners, and members of the public in a virtual journal club setting. The increasing number of impressions, participants, and tweets during #firesidetox demonstrates the tweetchat model to discuss pertinent toxicology topics is feasible and well received among its participants.